Advance in green synthesis of pharmacological important heterocycles using multicomponent reactions and magnetic nanocatalysts (MNCs) - Digafie Zeleke; Tadewos Damena (Results in Chemistry, 2024)
The ever-increasing environmental pollution and its health concerns appeal replacement of conventional organic synthesis with green synthetic methodology. This review presented detailed overview of the green synthesis of pharmacological important heterocycles in the last five years. The reactions discussed herein characterized by high atomic economy, excellent isolated yield, occur in relatively short time, and use green solvents at mild reaction conditions. It provided a detailed discussion about the application of multicomponent reactions and recyclable magnetic nanocatalysts in green synthesis of pharmacological important heterocyclic scaffold. The importance and the principles of green synthesis have been highlighted. Similarly, the preparation, the recovery and recyclability of magnetic nanocatalyst composites were explained. The dual advantage of employing inexpensive and biodegradable biopolymers as a composite of magnetic nanocatalyst was emphasized. The scope and the effectiveness of the designed synthetic methodologies as well as the potential uses of the synthesized heterocycles were discussed. In addition, the ecofriendly properties of the reactions and the work up process also have been elaborated.